Family and gender relations - Melo , Alana Silva de (Seven Editora, 2023)
Within academic studies, approaches to the concept of gender present different perspectives of analysis, in the same way, that there is also a huge confusion of understanding of the term within the general population. For this reason, then, I seek to build with a brief contextualization of its historical evolution. Gender and family are complex issues, and traditionally societies have tended to have rigid gender roles in which men played the role of providers, women as caregivers of the home and children, and the family would be a property result of patriarchy. Faced with a society that imposes conditions that determine what is female or male, I broaden the discussion on psycho-pedagogical development, bringing light to facts that are determinant for children's development, emphasizing the importance of offering an environment that allows children to explore the potentialities regardless of gender expectations that limit learning by classifying the activities of boys and girls bringing impacts to the development of skills, self-confidence, and self-esteem prevent equitable learning opportunities which do not contribute to a balanced society. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-002